Silica-Coated ZnS Quantum Dots for Multicolor Emission Tuning from Blue to White Light - Saavedra Rodríguez, Gerardo; Chapa, Christian; Sanchez Zeferino, Raul; Alvarez Ramos, Mario Enrique (2021)
The present work reports the easy tunability from blue to cold-white light emission of ZnS quantum dots embedded into a silica matrix (ZnS@SiO2) by simple heating treatments (up to 900 °C) without the need of rare earth or heavy metal ion doping. The heating causes gradual changes in the composition of samples, such as crystallization of cristobalite and formation of zinc silicate, whose optical properties contribute to the tunability of the material. The evolution of the induced changes in the shape and structure was followed by scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman and Fourier transformed infrared spectroscopies. Diffuse reflectance and photoluminescence spectroscopies were used to analyze the optical properties of the obtained materials, exhibiting that as-synthesized ZnS@SiO2 nanoparticles have an intense and wide blue emission band centered around 440 nm under 325 nm excitation, which is modified by the temperature with the enhancement of the intensity and widening of the band emission, as well as maximum shifting. The calculations of the CIE 1931 chromaticity coordinates show the tuning of the precepted tonality of the emission color from ocean-blue (0.18, 0.14) up to blue-sky (0.20, 0.31) and cold white light (0.27, 0.33) with a correlated color temperature of 12 500 and 7400 K for the last two. Besides suitable and facile tuning of the color emission, the thermal treatment of samples increases the stability of each one allowing their long-term usage as emitting devices.